Environmental Health Risk Analysis Around the Banjarbakula Landfill Using the HIRADC Approach - Irfa'i, Muhammad; Haris, Abdul; Adiansyah, Adiansyah; Pahruddin, Muhammad; As, Zufikar Ali; Imanuddin, Muhammad Rizki (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2026)
Landfills are a critical component of urban solid waste management systems; however, when inadequately managed, they may pose substantial risks to environmental quality and public health in surrounding communities. This study aimed to analyze environmental quality and public health risks in the vicinity of the Banjarbakula Landfill. A descriptive–analytic cross-sectional design was employed, integrating measurements of ambient air quality, groundwater quality, and soil quality at selected locations around the landfill with a community health survey. Risk analysis was conducted using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. The results indicated that concentrations of landfill gases and airborne particulates exceeded environmental quality standards, while groundwater and soil samples were contaminated with heavy metals, including lead, mercury, and cadmium. The community health survey revealed a high prevalence of respiratory disorders, skin diseases, and gastrointestinal disturbances, particularly among residents living closer to the landfill site. Risk assessment identified chemical and biological hazards as the dominant risks, classified as high risk. These findings demonstrate that the management of the Banjarbakula Landfill still requires significant improvements to reduce environmental degradation and public health risks. This study provides a scientific basis for strengthening policy implementation, enhancing landfill management technologies, and improving public health protection in communities surrounding landfill areas.